(3GdeGdjI GdOhdjI (B:s (3GdYedGJ GdGLfHjI h GdeTJbGJ GdeGdjI Hjf GdfXQjI h GdJWHjb (B/s - (3cfL TcQj, eGgQs; (3YhV, eQhGf s ((3YeGf(B: s (3eYgO GdOQGSGJ GdeUQajI(B, s, 2004)
(3fXGe GdfbO GdOhdj heUGOQ GdJehjd GdOhdj eY GdJehjd GdOhdj bUjQ GdCLd `` GdShb GdfbOjI , GdJehjd GdOhdj eJhSW h Whjd GdGLd Shb QCS GdeGd HGdJWQb Gdi GdSfOGJ h GdbQhV GdeLeYI , CShGb GdJehjd GdOhdjI GdKGfhjI h GdJYGed HGdYedGJ GdGLfHjI h SYQ GdUQah cPdc Shb GdYedGJ GdGLfHjI GdGfjI h GdGLdI Ke GdJWQb Gdi GdeTJbGJ GdeGdjI h Pdc HJfGhd GdYbhO GdeSJbHdjI h Mbhb GdNjGQ h CNjQG YedjI GdJHOjd Ch GdebGjVGJ (B.s
Keywords: (3GdJehjd GdOhdjs; (3GdYedGJ GdCLfHjIs; (3GdeGdjIs; (3fXGe GdfbO GdOhdjs